2020
DOI: 10.2147/ijn.s269340
|View full text |Cite
|
Sign up to set email alerts
|

<p>Formulation, Cellular Uptake and Cytotoxicity of Thymoquinone-Loaded PLGA Nanoparticles in Malignant Melanoma Cancer Cells</p>

Abstract: Introduction: Thymoquinone (TQ) is the main active compound extracted from Nigella sativa a traditional herb with wide therapeutic applications and recognizable anticancer properties. This study aimed to formulate and characterize TQ-nanoparticles using PLGA as a biocompatible coating material (TQ-PLGA NPs) with the evaluation of its therapeutic properties in human melanoma cancer cells. Methods: The TQ-PLGA NPs were prepared and characterized for size, zeta potential, encapsulation efficiency, and release pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…A cubosomal formulation of TQ improved cellular accumulation, which leads to increased apoptotic activity migration in mammary gland carcinoma cell lines (MDA-MB-231 and MCF-7) [ 187 ]. Chitosan-coated TQ-PLGA-NPs accumulated in melanoma cancer cells (A375) by taking advantage of the EPR effect and positive surface charge of chitosan, which facilitate binding with the negatively charged cell membrane and induce cellular retention as well as time-dependent cytotoxicity [ 188 ]. TQ loading into niosomes improved cellular internalizations with controlled release of TQ, which markedly inhibits the migration of pro-inflammatory markers in mammary gland carcinoma with respect to pure TQ [ 10 ].…”
Section: Neoplasm and Its Pathogenesismentioning
confidence: 99%
“…A cubosomal formulation of TQ improved cellular accumulation, which leads to increased apoptotic activity migration in mammary gland carcinoma cell lines (MDA-MB-231 and MCF-7) [ 187 ]. Chitosan-coated TQ-PLGA-NPs accumulated in melanoma cancer cells (A375) by taking advantage of the EPR effect and positive surface charge of chitosan, which facilitate binding with the negatively charged cell membrane and induce cellular retention as well as time-dependent cytotoxicity [ 188 ]. TQ loading into niosomes improved cellular internalizations with controlled release of TQ, which markedly inhibits the migration of pro-inflammatory markers in mammary gland carcinoma with respect to pure TQ [ 10 ].…”
Section: Neoplasm and Its Pathogenesismentioning
confidence: 99%
“…These studies revealed that THQ has a variety of important mechanisms of action in cancer treatment, such as inducing apoptosis in cancer cells by generating reactive oxygen species (ROS), interfering with DNA structure and synthesis, acting as an immunomodulator, and targeting carcinogenic signaling pathways [9][10][11]. Nanotechnology-based delivery platforms have demonstrated promise in the treatment of cancer due to their enhanced permeability and retention (EPR) properties, which facilitate drug targeting to cancerous cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene-coated AgNP caused few genetic changes compared to uncoated NPs based on cell viability assay, micronucleus test, and DNA microarray analysis [ 187 ]. Thymoquinone PLGA (TQ-PLGA) NPs formulated and characterized using an active compound extracted from Nigella sativa – TQ is a biocompatible coating material (TQ-PLGA NPs) with the evaluation of its therapeutic properties in human melanoma cancer cells with 96.8% encapsulation efficiency [ 188 ]. Other evidence demonstrates that AgNP coatings interfere with normal healthy skin cells.…”
Section: Strategies To Overcome Toxicitymentioning
confidence: 99%